Evaluation of Maternal Reproductive Outcomes and Biochemical Analysis from Wistar Audiogenic Rats (WAR) and Repercussions in Their Offspring - Moraes-Souza, Rafaianne Q. [UNESP]; Sinzato, Yuri K. [UNESP]; Antunes, Beatriz T. [UNESP]; Umeoka, Eduardo H. L.; Oliveira, José Antônio C.; Garcia-Cairasco, Norberto; Karki, Barshana; Volpato, Gustavo T.; Damasceno, Débora Cristina [UNESP] (Springer Nature, 2020)
The objective of the present study was to evaluate maternal reproductive performance, body weight, and frequency of external and internal anomalies of newborns of Wistar Audiogenic Rat (WAR) females as compared with Wistar rats. The adult WAR and Wistar rats were mated within their respective strains. After confirming the pregnancy, the body weights were weekly evaluated. On day 21 of pregnancy, the female rats were anesthetized and sacrificed to evaluate the maternal reproductive outcomes and biochemical profile, newborn weight, and external and internal anomalies. The WAR strain gained less weight during the pregnancy and presented hyperproteinemia, hypertriglyceridemia, and embryonic losses concerning Wistar rats, suggesting an inadequate intrauterine condition for embryonic development and fetal viability. WAR also presented a higher percentage of newborns classified as small for gestational age related to intrauterine growth restriction, which was confirmed by the lower number of ossification centers. There was a higher percentage of skeletal anomalies compared with fetuses of the Wistar dams, confirming their greater susceptibility during the formation and development of their skeletal system. Thus, the WAR presents physiological alterations compromising the viability of their embryos and fetuses, leading to impaired development of the newborns.
Keywords: Anomalies; Audiogenic seizure; Biochemical parameters; Pregnancy; Rodents